Análise mineralógica, correlações e implicações na formação de Neossolos de uma topossequência - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
A toposequence represents a sequence of soils developed throughout different topographic positions in the landscape and the properties of the soils they are made of are mainly influenced by the topography. Neosols show little genetic development and present features that make them more susceptible to degradation processes such as erosion, mainly in areas of rugged landscape. This study aimed at investigating a toposequence of Neosols located in Baliza -GO, presenting three soil profiles classified as Quartzarenic Neosol, Litholic Neosol, and Fluvic Neosol. The study sought to identify possible correlations and implications of the mineralogy of the soils involved in that toposequence due to degradation processes. The hypothesis tested is that the physical, chemical, mineral and micromorphological properties of the Neosols result from interactions between the different profiles and horizons throughout the landscape, influenced by the transport of sediments and weathering processes. The tests carried out included physical, chemical, mineral, micromorphological, and statistical analyses to characterize the samples and understand their properties throughout the toposequence. The analysis techniques included He gas pycnometry, granulometric analysis, physical fractioning, dynamic light scattering, X-ray fluorescence, infrared spectrometry, X-ray diffraction, and the Rietveld Method, scanning electron microscopy, and determination of the estimated weathering indices. Data was interpreted by means of statistical analyses such as ANOVA, Tukey test, and Pearson correlation, which allowed the evaluation of significant differences between the horizons of each soil profile and between profiles and the identification of correlations between their properties. Based on the results, were possible to verify that the physical, chemical, mineral, and micromorphological properties of each profile, imply and correlate properties between the subjacent horizons of each profile and the toposequence adjacent profiles
Keywords: classificação textural; composição química elementar; quantificação mineral; análise estatística; análise microscópica; textural classification; elemental chemical composition; mineral quantification; statistical analysis; microscopic analysis; Física